The Development of SketchCa-based Animated Video Learning Media for Building Utility Construction Learning - Rahman, Aditia Nur; Widaningsih, Lilis; Susanti, Indah (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
The development of digital technology today is increasingly opening up opportunities for teachers to develop interactive learning media. So far, the use of learning media that utilises various digital applications has not been widely developed to assist students in understanding teaching materials and maximising digital literacy. This study aims to develop a SketchCa-based animated video learning media on cut-out image material in the Building Utility Construction subject in class XI, Department of Building Modeling and Information Design. The research method used is research and development (R & D). The development of this animated video learning media uses SketchUp and Canva software applications. The data collection technique in this study used a media and technology expert validation sheet. This research is still developing to obtain relevant media results from product feasibility tests by media and technology experts. This paper describes the stages of instructional media design and a literature review to analyse how this SketchCa-based animation media contributes to learning.